Data in support of global role of the membrane protease LonB in Archaea: Potential protease targets revealed by quantitative proteome analysis of a lonB mutant in Haloferax volcanii - Cerletti, Micaela (2015)
This data article provides information in support of the research article "Global role of the membrane protease LonB in Archaea: Potential protease targets revealed by quantitative proteome analysis of a lonB mutant in Haloferax volcanii" [1]. The proteome composition of a wt and a LonB protease mutant strain (suboptimal expression) in the archaeon Haloferax volcanii was assessed by a quantitative shotgun proteomic approach. Membrane and cytosol fractions of H. volcanii strains were examined at two different growth stages (exponential and stationary phase). Data is supplied in the present article. This study represents the first proteome examination of a Lon-deficient cell of the Archaea Domain.